A Didactic Intervention On Written Discourse And Rhetorical Patterns - Zárate Mejía, Esteban Juan Bautista; Páez Ruenes , Michel Jesús; Servín Medina, Antonio Mario; Sánchez García , Rafael (CV. AFDIFAL MAJU BERKAH, 2024)
Reading comprehension skills in EFL is vital for university students. Particularly, being aware of the writer’s intention by means of discourse patters allows students to interact with the written text. Therefore, this research paper examines the implementation of a Discourse Analysis perspective in an Intermediate general EFL lesson aimed to enhance both critical thinking and reading skills by identifying the use of language patterns in written texts. 20 students form an Upper-Intermediate English course that studies a BA in English at a public University situated in the center of the state of Veracruz Mexico were the participants. Qualitative classroom research approach was chosen to implement a didactic intervention aimed at enhancing students communicative and reflective skills on the impact that social media has had on their lives. Results revealed that students were able to identify the meaning, and the relationship discourse markers establish between the written ideas and the meaning the writer wants to transmit. Particularly, students were able to reflect on the implications of social media use on communication, information access, marketing, and self-perception of its users. The didactic implications of the lesson focused on discourse patterns use indicate that such teaching perspective can significantly improve students’ critical thinking and communicative abilities. Therefore, it can be considered this lesson as an innovative proposal for enhancing the development of communicative skills in EFL students.